Impacts of Butterworth post-filtering on absolute quantification of 99mTc SPECT/CT using nema phantom - Chi, Leah Tan Shin (Universiti Sains Malaysia, 2024)
Background: Absolute quantification of radiotracer distribution using SPECT/CT imaging is crucial for dosimetry and personalized radionuclide therapy. However, the accuracy of quantification depends on various factors. Using phantom measurements, this multi-vendor and multi-center study evaluated the quantitative accuracy and inter-system variability of different SPECT/CT systems, as well as the impact of patient size, processing software and reconstruction algorithms on recovery coefficients (RC). Method: The study utilized phantom measurements to assess the quantitative performance of the GE Discovery NM/CT 670 Pro SPECT/CT system. Tc-99m activity was prepared to achieve target-to-background ratios (TBR) of 4:1 and 10:1. The NEMA 2012/IEC 2008 phantom was used, and images were acquired, reconstructed, and analysed using the Xeleris workstation and Q. Metrix software. Metrics such as contrast, signal-to-noise ratio (SNR), and RC were evaluated under different Butterworth filter parameters. Results: The results showed that the choice of Butterworth filter parameters, specifically the cutoff frequency (COF) and power, had a significant impact on image quality and quantitative accuracy. For the TBR 10:1 scenario, the optimal Butterworth filter parameters were a COF of 0.8 cycle/mm and a power of 15, which produced the highest contrast and SNR. For the TBR 4:1 scenario, the optimal parameters were a COF of 0.8 cycle/mm and a power of 10. Conclusion: This study demonstrates the importance of carefully optimizing the Butterworth filter parameters in SPECT/CT imaging to achieve the best balance between image quality and quantitative accuracy. The findings can guide the selection of appropriate reconstruction settings for improved absolute quantification, which is crucial for applications such as dosimetry and personalized radionuclide therapy.